2018
DOI: 10.2147/ppa.s150679
|View full text |Cite
|
Sign up to set email alerts
|

A new pulmonary rehabilitation maintenance strategy through home-visiting and phone contact in COPD

Abstract: BackgroundThe benefit of pulmonary rehabilitation (PR) for patients with COPD diminishes over time. We investigated a new strategy involving home-visit and phone contact and compared this to usual care in maintenance of PR benefits.MethodsA total of 172 stable COPD patients receiving 8-week PR program were recruited for this prospective study. Patients were allocated into usual care group (UC) and PR maintenance group (PRMG) randomly. Patients in PRMG participated in maintenance strategy at home under supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Previous PR programs in COPD have reported an increase in functional capacity, decrease in symptom burden, reduced care dependency, and improvement in the quality of life. 25-30 On the contrary, it is important to note that few of these programs have been conducted by nurses. 31,32 Further nursing-driven programs are urgently needed because of high symptom burden, polypharmacy, repeated hospitalizations and high care dependency in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous PR programs in COPD have reported an increase in functional capacity, decrease in symptom burden, reduced care dependency, and improvement in the quality of life. 25-30 On the contrary, it is important to note that few of these programs have been conducted by nurses. 31,32 Further nursing-driven programs are urgently needed because of high symptom burden, polypharmacy, repeated hospitalizations and high care dependency in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in persons with COPD who had not already engaged in pulmonary rehabilitation support TC's feasibility, safety and efficacy [ 35 , 36 ]. The low-impact, adaptable movements and postures make TC particularly attractive for persons with COPD [ 37 , 38 ]. In a separate pilot randomised controlled trial (RCT) in patients with moderate–severe COPD, we demonstrated trends toward improvement in HRQL, depression and dyspnoea after 3 months of TC versus an education control group [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the subcategories of this category was patients’ limited access to PR services. Home visit for improving home environment and providing correct home-based services is a key component of PR for patients with COPD [ 42 ]. However, home visit is not performed in many developing countries, like Iran, resulting in patients’ limited access to some PR services and reduced effectiveness of PR [ 43 ].…”
Section: Discussionmentioning
confidence: 99%